Technical characteristics of Poltava polygon of solid waste and the state of soil and air of populated areas - Молчанова, А. В. (Scientific Progress & Innovations, 2018)
There are no significant changes in the work of Poltava polygon of solid waste. Thus, during the last 5 years nothing was done, except the purchase of 4 bulldozer machines and the installation of automobile scales. The amount of accumulated livelihoods increases. Therefore, the problem of waste management is one of the key environmental problems.